Perbaikan Sistem Pelacakan Panel Surya Menggunakan Penyesuaian Posisi Massa Tambahan - Ericson Rajagukguk (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2022)
This study aims to obtain an effective solar panel tracking mechanism using energy-efficient electric actuators. Furthermore, we designed and implemented a semi-active solar tracking system. A tracking system is proposed to control solar panel orientation using a moving mass, a spring system, and an actuator. The weight of the moving mass and the spring constant are optimized to reduce actuator size. A stepper motor was used for this case. This electric drive is not the prime mover of the solar tracker; hence, it works against mass elements lighter than solar panel weight as used in the active solar tracker. Experimental results suggest that the average power required by the stepper motor is 0.21% of the energy generated by the solar tracking system. The results indicate that the proposed solar panel tracker works satisfactorily to control solar panel orientation.